2021
DOI: 10.3390/ijerph18042133
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Food Fortification in Improving Nutritional Status of Mothers and Children in Indonesia

Abstract: Food fortification programs have been conducted in several countries to overcome micronutrient deficiency and related problems with various degrees of effectiveness. Available information regarding the success of food fortification programs in some developing countries, including Indonesia, is still limited. Thus, this study conducts a systematic review of the effects of food fortification of mothers and children using biochemical and anthropometric measures focusing on linear growth. Three databases were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
0
15
0
4
Order By: Relevance
“…Whilst iron fortification of wheat flour has been mandatory in Indonesia since 2001 (44) consumption of wheat flour products among adults in our study was very low; the dominant carbohydrate source was white rice (45) . Only recently has iron fortification of rice programs began in Indonesia, but with limited success in increasing serum hemoglobin and ferritin levels (44) .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Whilst iron fortification of wheat flour has been mandatory in Indonesia since 2001 (44) consumption of wheat flour products among adults in our study was very low; the dominant carbohydrate source was white rice (45) . Only recently has iron fortification of rice programs began in Indonesia, but with limited success in increasing serum hemoglobin and ferritin levels (44) .…”
Section: Discussionmentioning
confidence: 83%
“…Whilst iron fortification of wheat flour has been mandatory in Indonesia since 2001 (44) consumption of wheat flour products among adults in our study was very low; the dominant carbohydrate source was white rice (45) . Only recently has iron fortification of rice programs began in Indonesia, but with limited success in increasing serum hemoglobin and ferritin levels (44) . The added health benefits of soybean should also be mentioned, including a recent study that found that a drink made from soybean protein had anti-inflammatory properties among pregnant women in Malaysia (46) .…”
Section: Discussionmentioning
confidence: 83%
“…The impact of babies with low birth will last from generation to generation; children with LBW will have fewer anthropometric measurements in their development [17]. The continued impact of low birth weight (LBW) can be in the form of failure to thrive, and if a baby is born with LBW, it should be anticipated that it will be challenging to catch up with average early growth and may cause the child to become stunted as one of the risks [18]. Supplementary feeding that does not focus on the frequency, texture, timing of feeding, and diversity can cause stunting in under-five children.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alternative efforts such as food fortification become important to do, especially in snacks that are mostly preferred by teenagers. In addition to promising results in terms of decreasing the problem of micronutrient deficiency (Dewi et al, 2021), fortification in snacks is also potentially effective because adolescents aged 18-25 years tend to consume snacks ≥3 times per day which contributes to 25% recommended dietary allowance (RDA) or average daily dietary intake level (USDA, 2012).…”
Section: Introductionmentioning
confidence: 99%